2020
DOI: 10.2147/cmar.s249540
|View full text |Cite
|
Sign up to set email alerts
|

<p>Further Understanding of High-Grade Serous Ovarian Carcinogenesis: Potential Therapeutic Targets</p>

Abstract: High-grade serous ovarian carcinoma (HGSOC) is the most common type of ovarian cancer and the most lethal gynecologic malignancy due to advanced stage at presentation. Recent years have witnessed progress in the therapy of HGSOC with the introduction of PARP (poly-adenosine diphosphate ribose polymerase) inhibitors and the anti-angiogenic monoclonal antibody bevacizumab to the backbone of chemotherapy or as maintenance therapy after chemotherapy. The improved molecular understanding of ovarian cancer pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 115 publications
(149 reference statements)
1
0
0
Order By: Relevance
“…In our in vitro studies, we observed that a treatment of cells with paclitaxel/adavosertib was very effective in killing Ovcar4-BRD4-L and Ovcar4-BRD4-S cells. Our findings are consistent with previous studies showing that the adavosertib effectively inhibits ovarian cancer growth as a single agent in preclinical studies [ 61 ], and improves disease outcome of platinum-resistant ovarian carcinoma patients (evaluated in phase II clinical trials) [ 62 64 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our in vitro studies, we observed that a treatment of cells with paclitaxel/adavosertib was very effective in killing Ovcar4-BRD4-L and Ovcar4-BRD4-S cells. Our findings are consistent with previous studies showing that the adavosertib effectively inhibits ovarian cancer growth as a single agent in preclinical studies [ 61 ], and improves disease outcome of platinum-resistant ovarian carcinoma patients (evaluated in phase II clinical trials) [ 62 64 ].…”
Section: Discussionsupporting
confidence: 92%